Factores de riesgo de las enfermedades cardiovasculares en el personal de la Universidad Peruana Unión, 2009. - Quiliche Castañeda, Ruth Beatriz (2019)
Objective: Identify risk factors for cardiovascular disease (CVD) on the staff of the Universidad Peruana Union,2009. Methodology: Cross-sectional, descriptive, analytic in a sample of 36 people from 30 to 65 years who wereassessed CVD risk factors: nutritional status, dietary, physiological, lifestyle and stress. Results: Nutritional status,BMI 38.8% 22.2% overweight and obesity, waist-hip ratio 72.2% at risk of central obesity, percent body fat 75%in obesity. Dietary, increased energy intake (55.6%) and vitamin C, reduced contribution of monounsaturated fattyacids (80.5%), polyunsaturated (11.1%) and fiber (97.2%) and lower water consumption (80 , 6%). Physiological,elevated total cholesterol 36.1%, LDL-C 33.3%, triglycerides and homocysteine 61.1% 11.1%, and decreased values of HDL-C 22.2%. Lifestyle, 61.1% were sedentary and 86.1% rated moderate stress. 40% of all men will havemore than six factors compared with women 17%. Conclusion: More than half with a BMI above normal, threequarters of the participants at risk of central obesity as waist-hip and fat and risk of obesity in almost everyone. Inmore than half of the participants provided more energy diet and mostly protein and lipids in the diet over threequarters of the participants showed a higher intake of vitamin C and reduced water consumption, the evaluationshowed sub suitability for monounsaturated fatty acids and fiber of almost all, in a tenth of them were adequate forpolyunsaturated fatty acids. In the third part of the participants noted high levels of TC and LDL-C, in the quarterdecreased values of HDL-C, in the middle elevated TG, in the tenth elevated homocysteine. Also more than half ofthe participants are in a sedentary condition and almost all rated in moderate stress. Finally, about half of all menwill have more than six coronary risk factors and on the fifth of women